Implicit Contracts, Incentive Compatibility, and Involuntary Unemployment. - MacLeod, W; Malcomson, J (Department of Economics (Queen's University), 1986)
This paper characterizes all outcomes supportable by implicit employment contracts of the most general form when employee's performance is not public information. A strictly positive economic surplus must result from employment, the form of contract depending on how this surplus is divided between firm and employee. In a general equilibrium formulation with more workers than job vacancies, the surplus goes to employed workers giving them strictly higher utility than unemployed workers who are, therefore, involuntarily unemployed. With more job vacancies than workers, the surplus goes to firms with workers, giving them strictly positive profit despite there being unfilled vacancies.